Functional-semantic paradigms of voice сategory in the Kazakh language - Gaziza ImanaliyevaАnarkul Salkynbay, Nazyken Yegizbaieva, Shaigul Ramazanova, (Opción, 2019)
The purpose of the article is to define the formal and semantic system of voice category, their syntactic, communicative and semanticpragmatic functions via comparative qualitative research methods. As a result, there is no difference between the paradigms of the form of the personal voice and impersonal voice categories in the structure and meaning. In conclusion, the resulting (static) meaning of an impersonal voice category form may indicate that the subject is not in the initial position and changes in the aspectual value.